Ge-Sb-Te Chalcogenide Thin Films Deposited by Nanosecond, Picosecond, and Femtosecond Laser Ablation - Bulai, Georgiana; Pompilian, Oana; Gurlui, Silviu; Němec, Petr; Nazabal, Virginie; Cimpoesu, Nicanor; Chazallon, Bertrand; Focsa, Cristian (MDPI AG (Multidisciplinary Digital Publishing Institute), 2019)
Ge-Sb-Te thin films were obtained by ns-, ps-, and fs-pulsed laser deposition (PLD) in various experimental conditions. The thickness of the samples was influenced by the Nd-YAG laser wavelength, fluence, target-to-substrate distance, and deposition time. The topography and chemical analysis results showed that the films deposited by ns-PLD revealed droplets on the surface together with a decreased Te concentration and Sb over-stoichiometry. Thin films with improved surface roughness and chemical compositions close to nominal values were deposited by ps- and fs-PLD. The X-ray diffraction and Raman spectroscopy results showed that the samples obtained with ns pulses were partially crystallized while the lower fluences used in ps- and fs-PLD led to amorphous depositions. The optical parameters of the ns-PLD samples were correlated to their structural properties.
Chalkogenidové tenké vrstvy Ge-Sb-Te deponované nanosekundovou, pikosekundovou a femtosekundovou laserovou ablací
Keywords: pulsed laser deposition; chalcogenide thin films; spectroscopic ellipsometry; pulzní laserová depozice; chalkogenidové tenké vrstvy; spektrální elipsometrie